Ewolucja ustawodawstwa i orzecznictwa Sądu Konstytucyjnego Ukrainy w kwestii języka państwowego - Czachor, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The language issue was among the most salient problems of Ukrainian public life since gaining independence in 1991. There is no doubt that it was one of the crucial factors that influenced Ukrainian politics and driving its dynamics. National parties have advocated for declaring the Ukrainian language as the sole official language and in doing so eliminating the Russian language from the public space. The Communists and parties personally and financially related to pro-Russian parties have tended to value the Russian language to preserve bilingualism and even maintain its factual dominance in everyday life. The goal of the this paper is to provide a retrospective overview of the evolution of the legal framework of the Ukrainian language policy after 1991. It focuses on the legal acts regulating the status of the state language of Ukraine and the most significant judgments of the Ukrainian Constitutional Court. This problem until now was not addressed by the Polish scientific literature. The main thesis of the article asserts that despite the Ukrainian law and constitutional jurisprudence stipulating and supporting unilingualism, it has not been as radical and consistent as that of the Baltic states, for example. The change in the attitude of the Ukrainian authorities and their consistent efforts to solidify the Ukrainian language in the public sphere can be traced back to the so-called Euromaidan (“the revolution of dignity”) in 2014. The most significant step in these efforts was done in 2019 by the adoption of the new bill that exhaustively regulated the status of Ukrainian as the state language and the only mean of communication in official proceedings and the public sphere. The law has consequently led to the elimination of bilingualism in the public sphere, including education and mass media. Similarly, the standpoint of the Constitutional Court has evolved. In the first two decades of independence it represented a moderate position in case of the language issues, avoiding their clear resolution; however, since the second decade of the 21st century it decisively articulates the importance of Ukrainian as the state language and its role in the consolidation of the national state.
Keywords: constitutional law of Ukraine; constitutional jurisprudence in Ukraine; language policy of Ukraine; language as a subject of law regulations; konstitucìjne pravo Ukraïni; konstitucìjne sudočinstvo Ukraïni; movna polìtika Ukraïni; mova âk predmet pravovogo regulûvannâ